MENGGAGAS KONSEP PENERAPAN SHARIAH COMPLIANCE AUDIT: SEBUAH UPAYA PENCAPAIAN ISLAMIC CORPORATE GOVERNANCE - Prakosa, N. Iman; Zuchri, Lutfi (Jurnal Ekonomi & Keuangan Islam, 2011)
This research is aimed to give solution over the imbalance that happened between the practices that shariah business entities actually do and those that should be done. This research will formulate an ideal concept regarding shariah compliance audit which involves independent party outside the company structureâ€”the independent party suggested in this research is Certified Shariah Public Accountant (APSB)â€”who will assess the fairness of shariah business entity practices in accordance with Indonesian Generally Accepted Principals of Shariah Business Practices (PPBSBUI). Then hopefully there would be no more public deception upon â€œshariahâ€ label on shariah business entities and the islamic corporate governance on shariah business entities will be accomplished as well.